Clinical application of regional citrate anticoagulation for membrane-based therapeutic plasma exchange in children with liver failure - Hu, Jun; Wang, Chunxiao; Bai, Ke; Liu, Chengjun (Frontiers in Pediatrics, 2023)
Background: Few reports describe the application of membrane-based therapeutic plasma exchange (mTPE) with RCA in children with liver failure (LF). Aims: To explore the application of RCA-mTPE in children with LF. Methods: We retrospectively analyzed data from children with LF who underwent RCA-mTPE in the Children’s Hospital . We used the total to ionized calcium ratio (T/iCa) > 2.5 as the diagnostic criteria for citrate accumulation (CA). The patients were divided into two groups according to the occureence of CA at the end of RCA-mTPE (CA group: T/iCa>2.5; NCA group: T/iCa≤2.5).To evaluate the clinical safety and efficacy of RCA-mTPE, the following data from medical records were assessed and compared between groups: clinical characteristics, reasons for LF, RCA-mTPE parameters and duration, laboratory findings, and complications. Results: In total, 92 RCA-mTPE treatments were administered to 21 children with LF over 3.8 ± 0.9 hours. The following mean values were determined: blood flow rate(QB),=2.8 ml/kg/min, 4% sodium citrate dose/blood flow rate ratio(QCi/QB)=1.1(QCi,ml/kg/h); plasma dose/body weight ratio(QP/BW)=18.5 (QP, ml/kg/h); 10% calcium gluconate dose/blood flow rate ratio(QCa/QB),=0.2(QCa, ml/kg/h). The mean concentration of iCa in vitro was 0.38 ± 0.07 mmol/L. Citrate accumulation was recorded after 34 (37%) treatments. Hypocalcemia occurred 11 (12%) and 7 (7.6%) treatments, during and after mTPE, respectively. Three hypotensive and one convulsive events (，related to hypocalcemia)， and two clotting events occurred during RCA-mTPE. After RCA-mTPE, the patients’ pH, HCO3- and Na+ levels, and T/iCa were significantly increased and the total bilirubin (TB), conjugated bilirubin(DB), prothrombin time (PT) , activated partial thromboplastin time(APTT), alanine aminotransferase (ALT), aspartate aminotransferase (AST),and ammonia levels were significantly decreased. The TB, DB, and lactic acid levels, before RCA-mTPE, were significantly higher in the CA group than in the NCA group, but there were no significance between the two groups in the blood flow rate/body weight (QB/BW), sodium citrate dose/blood flow rate (QCi/QB), and plasma dose/body weight ratio(QP/BW), mTPE duration, and estimated amount of citrate metabolized . Conclusions: Children with LF undergoing RCA-mTPE are at risk of hypocalcemia. With proper protocol adjustment, however, RCA-mTPE can be used safely and effectively in these patients.